Case report: Complete response of a bladder cancer patient with multiple hepatic and pelvic metastases treated by nab-paclitaxel combined with sintilimab - Tao, Zhu-lei; Wu, Wei; Liang, Lin-chun; Pan, Jin-feng; Cao, Jian-zhou; Jia, Xiao-long; Fang, Li; Ma, Qi (Frontiers in Oncology, 2022)
This article described a patient with metastatic bladder cancer (mBC) who was successfully treated with nab-paclitaxel plus sintilimab for the first-line treatment. Muscle-invasive bladder cancer (MIBC) was discovered in a 56-year-old man who received radical cystectomy and platinum-based adjuvant chemotherapy. Eleven months after cystectomy, this patient developed numerous hepatic and pelvic metastases and progressed to mBC. The patient was given an anti-PD-1 antibody (sintilimab 200mg, q3w) in combination with Nab-paclitaxel (100mg, qw) as first-line therapy for mBC. Complete remission (CR) was achieved after nine cycles of therapy, and the patient had no severe side effects during the treatment. The disease remained in CR after 34 months of follow-up. This case suggests that nab-paclitaxel combined with PD-1 may be a safe and effective option for the first-line treatment of mBC.